Pregunta
Suppose that the functions \( q \) and \( r \) are defined as follows. \[ \begin{array}{l}q(x)=3 x-2 \\ r(x)=4 x+5\end{array} \] Find the following. \[ (r \circ q)(-1)=\square \]
Ask by Curry Hills. in the United States
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\((r \circ q)(-1) = -15\)
Solución
To find \((r \circ q)(-1)\), we need to evaluate the functions \(q\) and \(r\) in succession.
1. **First, evaluate \(q(-1)\):**
\[
q(x) = 3x - 2 \\
q(-1) = 3(-1) - 2 = -3 - 2 = -5
\]
2. **Next, use the result from \(q(-1)\) as the input for \(r\):**
\[
r(x) = 4x + 5 \\
r(-5) = 4(-5) + 5 = -20 + 5 = -15
\]
Therefore, \((r \circ q)(-1) = -15\).
\[
\rboxed{-15}
\]
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Bonus Knowledge
To find \((r \circ q)(-1)\), we need to first evaluate \(q(-1)\) and then substitute that result into \(r\). Starting with \(q(-1)\): \[ q(-1) = 3(-1) - 2 = -3 - 2 = -5 \] Now we can find \(r(q(-1)) = r(-5)\): \[ r(-5) = 4(-5) + 5 = -20 + 5 = -15 \] Therefore, \((r \circ q)(-1) = -15\). The final answer is: \[ (r \circ q)(-1) = -15 \]
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium